Anal human papillomavirus in HIV-uninfected men who have sex with men: incidence and clearance rates, duration of infection, and risk factors. (December 2016) - Donà, M.G.; Vescio, M.F.; Latini, A.; Giglio, A.; Moretto, D.; Frasca, M.; Benevolo, M.; Rollo, F.; Colafigli, M.; Cristaudo, A.; Giuliani, M.
Abstract: Little is known regarding the natural history of anal human papillomavirus (HPV) infection. We aimed to evaluate incidence and clearance rates, their risk factors, and duration of anal HPV infection in HIV-uninfected men who have sex with men (MSM). A longitudinal study was conducted. Anal samples were analysed using the Linear Array HPV Genotyping test. Incidence and clearance rates, and corresponding risk factors, were estimated using a two-state Markov model. Overall, 155 MSM (median age 33.4 years) attending the largest sexually transmitted infection (STI) centre in Rome, Italy, were followed for a median of 12.2 months (Q1–Q3: 7.0–18.1). Incidence and clearance rates for any HPV were 85.6 (95% CI: 58.4–125.4) and 35.6 (95% CI: 24.7–51.5) × 1000 person-months, respectively; the median duration of infection was 9.4 months (Q1–Q3: 7.5–12.1). Receptive anal sex emerged as the only risk factor for the acquisition of any HPV (Hazard Ratio, HR = 2.65, 95% CI: 1.16–6.06). The incidence rates for carcinogenic and non-carcinogenic types were 42.3 (95% CI: 29.2–61.4) and 29.2 (95% CI: 19.5–43.7) × 1000 person-months, respectively (p = 0.13); their clearance rates were 62.9 (95% CI: 45.1–87.7) and 65.7 (95% CI: 47.4–91.0) × 1000 person-months, respectively (p = 0.83). HPV16 showed the lowest clearance rate among carcinogenic types (59.7 × 1000 person-months), and a duration of infection of 16.8 months. In conclusion, a higher incidence rate was observed for carcinogenic compared to non-carcinogenic HPV types, although the difference was not significant. HPV16 emerged as the type with the longest duration of infection and the lowest clearance rate among carcinogenic types.